2020
DOI: 10.21668/health.risk/2020.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Studying the contamination of tea and herbal infu-sions with myсotoxins (Message 2)

Abstract: Федеральный исследовательский центр питания, биотехнологии и безопасности пищи, Россия, 109240, г. Москва, Устьинский проезд, 2/14 Представлены результаты скрининга широкого спектра микотоксинов с помощью высокоэффективной ультра высокоэффективной жидкостной хроматографии в сочетании с тандемной масс-спектрометрией (УВЭЖХ-МС / МС) в различных видах чая представленных на рынке РФ. Образцы отобраны в торговой сети и предоставлены оптовыми поставщиками. Из 77 исследованных образцов: 54 нефасованные (полуфабрикат)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…Kiseleva et al (2020) found STC levels below the LOD in one black tea sample and six herbal blends (concentrations ranging between <4 and 10.0 µg kg −1 ) collected from tea markets in the Russian Federation, whereas no traces of this mycotoxin were found in the green and Pu-erh teas included in this recent study [ 58 ]. The co-occurrence of both AFs and STC in the present study in mycotoxin-positive green teas ( n =3), Pu-erh teas ( n = 3), and mycotoxin-rich peppermint tea raises concerns over their possible cumulative effects, which should be taken into account when evaluating mycotoxins’ impacts on human health.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Kiseleva et al (2020) found STC levels below the LOD in one black tea sample and six herbal blends (concentrations ranging between <4 and 10.0 µg kg −1 ) collected from tea markets in the Russian Federation, whereas no traces of this mycotoxin were found in the green and Pu-erh teas included in this recent study [ 58 ]. The co-occurrence of both AFs and STC in the present study in mycotoxin-positive green teas ( n =3), Pu-erh teas ( n = 3), and mycotoxin-rich peppermint tea raises concerns over their possible cumulative effects, which should be taken into account when evaluating mycotoxins’ impacts on human health.…”
Section: Discussionmentioning
confidence: 88%
“…While only a few recent studies have included Fusarium and Alternaria mycotoxins in their surveys for tea contamination, 1D-LC-MS mostly indicated a low sensitivity and issues related to the proper separation of 3-AcDON and 15-AcDON [ 58 ], as well as the need for multistep sample preparation to overcome these issues [ 15 ]. The developed 2D-LC method, which was applied within the present study, notably improved the separation efficiency of different DON metabolites and other challenging mycotoxins [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations